Efisiensi Pemasaran Kopi Robusta di Desa Harjokuncaran Kecamatan Sumbermajing Wetan Kabupaten Malang - Windasari, Adita; Rahaju, Juli; Mita Lestari, Adyla; Fitria Rahmawati, Mariana (Masyarakat Ekonomi Syariah Bogor, 2024)
Harjokuncaran village, Sumbermanjing Wetan Sub District is one of the coffee production centers in Malang regency and is able to compete with orther regions. The main problem marketing of robusta coffee in Harjokuncaran Village is that farmer can not determine their own selling price. The purpose of this study was to analyze the marketing effiiciency of robusta coffee that conducted the study from February to March 2018. Methods of data analysis used in this research are descriptive and quantitative. The results showed that there are 6 marketing channel with different marketing functions. The highest farmer share is on marketing channel II with a value 96,68%. The result of marketing efficiency analysis with price efficiency approach at can be said to be efficient. While the operational efficiency analysis on transportation function that is said to be efficient is on marketing channel I and marketing channel II because the percentage of transport capacity is more than 100%. And based on reseacrh, distance and farmer price are significantly affected to marketing marjin